2013
DOI: 10.3109/21691401.2013.841173
|View full text |Cite
|
Sign up to set email alerts
|

The liver-targeting study of the N-galactosylated chitosan in vivo and in vitro

Abstract: In order to study the liver targeting of the N-galactosylated chitosan (GC) polymer in liver, we first conjugated the lactobionic acid with chitosan (CS) to obtain the carrier of GC with different degree of substitution of lactosyl group. Western blot was performed to detect the expression levels of the asialoglycoprotein receptors (ASGPR) in the cell lines of HepG2, SMMC-7721, and HL-7702. The protein level of ASGPR was lower in HepG2 compared to HL-7702 and SMMC-7721. Although all treated by CS, viabilities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…Therefore, the plausible justification for the higher gemcitabine deposition in liver tissues might be due to the presence of galactose (asialoglycoprotein receptor ligands) on the nanoparticle surface, which might have provided specific and effective targeting to this organ. This observation is also in agreement with earlier reports wherein the drugloaded galactosylated chitosan nanoparticles successfully target the asialoglycoprotein receptor, which is overexpressed in HCC [23][24][25]. Reports also indicate that these galactosylated chitosan nanoparticles can enter cells through asialoglycoprotein receptor-mediated endocytosis, and show excellent efficacy in reducing tumor sizes in animal models [23][24][25].…”
Section: Blood Disappearance and Organ Distributionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, the plausible justification for the higher gemcitabine deposition in liver tissues might be due to the presence of galactose (asialoglycoprotein receptor ligands) on the nanoparticle surface, which might have provided specific and effective targeting to this organ. This observation is also in agreement with earlier reports wherein the drugloaded galactosylated chitosan nanoparticles successfully target the asialoglycoprotein receptor, which is overexpressed in HCC [23][24][25]. Reports also indicate that these galactosylated chitosan nanoparticles can enter cells through asialoglycoprotein receptor-mediated endocytosis, and show excellent efficacy in reducing tumor sizes in animal models [23][24][25].…”
Section: Blood Disappearance and Organ Distributionsupporting
confidence: 92%
“…This derivative contains galactose molecules, which are active ligands with specific liver targeting function. The prospective of galactosylated chitosan has been exploited as a liver-specific carrier to enhance the therapeutic efficacy of various drugs [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the strong hydrophilic nature of D-a-tocopherol polyethylene glycol 1000 succinate (TPGS), the drugs could be more completely released to improve the permeability, enhance the absorption in vivo and reduce P-glycoprotein (P-gp)-mediated multiple drug resistance (MDR) [13,14]. Additionally, because of the good emulsification properties of TPGS, NPs prepared with it had a smaller particle size and a higher drug-loading (DL) and encapsulation efficiency (EE) [15,16]. Because ASGPR has a high specificity and is highly expressed on the surface of liver parenchymal cells, the liver-targeting delivery drugs or the genes mediated by it have become a research focus in recent years [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, because of the good emulsification properties of TPGS, NPs prepared with it had a smaller particle size and a higher drug-loading (DL) and encapsulation efficiency (EE) [15,16]. Because ASGPR has a high specificity and is highly expressed on the surface of liver parenchymal cells, the liver-targeting delivery drugs or the genes mediated by it have become a research focus in recent years [16,17]. The glycoprotein binding of Gal or GalNAc residues can be identified by the ASGPRs, and the affinity of GalNAc for ASGPRs is approximately 50 times higher than that of Gal [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In the near future, more modified CS with encapsulated drugs or other conjugated excipients at C6 or both C2 and C6 could be prepared for more practicable pharmacotherapeutic strategies. In addition, toxicities of derivatives of CS in different human organs have not been completely understood although a lot of studies have been reported based on in vivo animal models (Archana, Dutta, & Dutta, 2013;Liang et al, 2014). However, there is no doubt that translation from animal models to humans is still difficult to achieve due to large differences of anatomical structures between animals and humans.…”
Section: Chitosan Nanoparticles As a Pulmonary Delivery Systemmentioning
confidence: 99%